2022
DOI: 10.3389/fvets.2022.979669
|View full text |Cite
|
Sign up to set email alerts
|

Urinary phoretograms performed by capillary electrophoresis in dogs with chronic disease with or without Leishmania infantum infection

Abstract: IntroductionThe study of early markers to detect kidney malfunction has increased in recent years since serum markers, such as creatinine increase when there is a 75% loss of renal mass. Urinary capillary electrophoresis (UCE) is an available laboratory technique that provides an easily interpretable electrophoretic pattern. This pattern in our study has been divided into five fractions as it is done in serum: fraction 1 migrating in the albumin zone, fraction 2 in the alpha1-globulins zone, fraction 3 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The lack of correlation between the serum and urinary fractions in G 1 may be attributed to the healthy status of the population and the expected low protein excretion in urine [40]. Previous studies have also reported a lack of association between serum and urine fractions in healthy dogs or dogs with kidney disease, where hypoalbuminemia is commonly observed [25].…”
Section: Comparison Between Urinary and Serum Electrophoretograms In ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The lack of correlation between the serum and urinary fractions in G 1 may be attributed to the healthy status of the population and the expected low protein excretion in urine [40]. Previous studies have also reported a lack of association between serum and urine fractions in healthy dogs or dogs with kidney disease, where hypoalbuminemia is commonly observed [25].…”
Section: Comparison Between Urinary and Serum Electrophoretograms In ...mentioning
confidence: 99%
“…It has proven to be a sensitive specific tool for detecting and characterizing different protein fractions in urine, including albumin, globulins, and other low-molecular-weight proteins [2][3][4]. Urinary capillary electrophoresis has been used in studies to assess proteinuria in dogs, providing information on protein profiles and possible alterations associated with renal and systemic diseases [25]. Instead, agarose gel electrophoresis is a widely used technique for separating proteins in biological samples.…”
Section: Comparison Between Urinary and Serum Electrophoretograms In ...mentioning
confidence: 99%
See 3 more Smart Citations